ANALISISÂ FAKTORÂ â€“Â FAKTORÂ YANGÂ MEMPENGARUHIÂ REALISASIÂ JUMLAHÂ PENERIMAANÂ PAJAKÂ HOTELÂ (Â StudiÂ padaÂ DinasÂ PendapatanÂ DaerahÂ KabupatenÂ TulungagungÂ ) - Alista, HerviaÂ NandaÂ (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
Hotel tax is one source of local ownâ€source revenue (PAD). The Government is trying to increase theirÂ of hotel taxes income Â in order to increase their Â local ownâ€source revenue (PAD). The research aims to analyzeÂ the influence of the number of tourists, the rate of inflation, and gross regional domestic product (PDRB) to theÂ hotel taxes income in Kabupaten Tulungagung for the period 2006â€2013. Â Â The data used Â are Â secondary data Â (time Â series) Â the Â for Â the period 2009â€2013 Â obtained Â from Â the LocalÂ Revenue Offices (DISPENDA) and the Central Bureau of Statistics (BPS) of Kabupaten Tulungagung. AmongÂ three Â variables, Â which Â were Â number Â of Â tourists, Â the Â rate Â of Â inflation Â and Â gross Â regional Â domestic Â productÂ (PDRB), the most dominant Â influential variable to the Hotel Taxes Income Â is gross regional domestic productÂ (PDRB). Â Based Â on Â this Â result, Â the Â researcher Â suggests Â to Â Government Â of Â Kabupaten Â Tulungagung Â mustÂ consider Â gross Â regional Â domestic Â product Â (PDRB) Â as Â the Â key Â indicator Â to Â improve Â Hotel Â Taxes Â Income Â inÂ Kabupaten Tulungagung.Keywords: Â Hotel Â Tax, Â Number Â of Â Tourists, Â The Â Rate Â of Â Inflation Â and Â Gross Â Regional Â DomesticÂ Product (PDRB)